Taxonomic study of bulbitermes (blattodea: termitidae: nasutitermitinae) in Sabah, Malaysia - Nivaarani Arumugam (2014)
This research was focused on the taxonomic studies of the genus Bulbitermes (family Termitidae and sub-family Nasutitermitinae) of Sabah. This study is important as morphological existing taxonomic information of Bulbitermes is not sufficient to separate the species. The objectives of this research were; 1) to study the morphological characters and revise the genus Bulbitermes of Sabah, and 2) to construct a pictorial identification key for the genus Bulbitermes of Sabah. Fresh specimens were collected manually at 11 different locations around Sabah using standardised belt transect method (100mx2m) and casual collection. In addition, preserved specimens of Bulbitermes from existing collection in BORNEENSIS, Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah were also analysed. A total of six described Bulbitermes species and nine morphospecies were examined in this study. Of these, a total of nine Bulbitermes species, one species from genus Ceylonitermes and one species from genus Lacessititermes were identified after revision. Of seven examined Bulbitermes morphospecies, four were confirmed to be similar with described species. Lacessititermes sp. and Ceylonitermes sp. were previously misidentified as Bulbitermes sp. G and Bulbitermes sp. F, respectively. This result gives rise to the 50% of Bulbitermes species in Sabah, comprising 27% of Bulbitermes species worldwide. Morphological characteristics of the species were analysed and the description of soldier caste and worker caste were given. Observation on the specimens from 425 colonies and cluster analysis using MultiVariate Statistical Package, (MVSP) showed that Bulbitermes sp. A and Bulbitermes sp. B are similar to B. constrictus. Meanwhile, Bulbitermes sp. C is similar to B. sarawakensis and Bulbitermes sp. D is similar to B. borneensis. These grouping clades have highest similarity value in cluster analysis. Bulbitermes sp. 1 is slightly similar to the B. germanus which have been recorded in Peninsular Malaysia but differs in the soldier mandible character where a distinct marginal teeth is present on both mandibles of Bulbitermes sp. 1 while this character is absent in the B. germanus. Bulbitermes sp. 2 and Bulbitermes sp. E could not be related with other Bulbitermes species which have been recorded in Malaysia. Bulbitermes sp. 2 comes closer to B. prabhae which have been identified in Thailand. Bulbitermes sp. E could not be related to any other Bulbitermes species due to the limitation in the morphological information and samples. Using the confirmed Bulbitermes species after revision, a pictorial identification key for the genus level and Bulbitermes species level were constructed. In conclusion, taxonomic status and list of Bulbitermes species for Sabah have been updated through this study. Hence, all these species give a rise to the total number of species and genera for Sabah. Research in molecular phylogeny could be conducted in the future to identify the genetic variance among these Bulbitermes species.